Assessment of Regulatory T Cells in Childhood Immune Thrombocytopenic Purpura. (5th November 2013) - Mazzucco, Karina L. M.; Junior, Lauro M.; Lemos, Natália E.; Wieck, Andréa; Pezzi, Annelise; Laureano, Alvaro M.; Amorin, Bruna; Valim, Vanessa; Silla, Lucia; Daudt, Liane E.; Marostica, Paulo J. C.
Abstract : This study had the objective to assess the frequency of Tregs in children newly diagnosed with ITP and ascertain whether an association exists between Tregs and platelet counts, by means of a comparison with healthy controls. This case-control study included 19 patients newly diagnosed with ITP—whose blood samples were collected at four points in time: before any therapy and 1, 3, and 6 months after diagnosis—and 19 healthy controls. Tregs (CD4 + CD25 + Foxp3 T cells) were evaluated by flow cytometry. There was a statistically significant difference in platelet count between the case and control groups. There were no significant differences in Treg counts between cases and controls at any point during the course of the study and no difference in Treg counts between the chronic and nonchronic groups and no significant correlation between Tregs and platelet counts in the case and control groups. The findings of this study did not show any statistically significant correlation between Tregs and number of platelets in the case and control groups. Treg cells did not play a role in the regulation of autoimmunity in children with ITP.